INTEGRASI NILAI NASIONALISME DALAM PEMBELAJARAN SEJARAH DI SEKOLAH MENENGAH ATAS NEGERI 1 TORAJA UTARA - Setiamin, Asnah Setiamin; Riang Tati, Andi Dewi Riang Tati (Universitas Muhammadiyah Palembang, 2024)
Students are the country's future generation, nationalism is crucial.Thus, the purpose of this study is to examine and summarise how North Toraja 1 State High School students cultivate nationalism via historical knowledge and other types of nationalism.This research uses a descriptive qualitative approach using historical research methods ,namely heuristics,criticism,interpretation and historiographycombined with questionnaires and observations in the schoolenvironment.The result of the research show that North Toraja State 1 High School student know nationalism well through learning history and the forms of activities carried out by students at school as a form of contemporary nationalism.